Rendimientos del maíz regadío : I. Parámetros asociados en el suelo aluvial de Mendoza (Argentina) - Nijensohn, León (1998)
In this work we took advantage of the great variability among replicates of the same fertilizer treatments in order to find relationships between soil characteris-tics and grain and stubble yield of eaeh plol. In this loamy alluvial soil of ca. 60 cm deep over the stony subsoil (pebbles, gravel.etc). The grain yield in the 12 non fertilized plots ranged between ca. 5 t/ha and 15 Uha, and the stubble between 7.75 Uha and 26,65 t/ ha. The general CV was 45%. The irrigation regime was optimized keeping the minimum available water at 30% of the total. Among the many soil characteris-tics studied total soil nitrogen (Nt) was the one that correlated most with the yield; P extracted with C02 satura-ted water at a 1: 1O relation (P-C02 1: 1O) and exchangea-ble potassium with amonium acetate (Ke-NH4) also showed some degree of correlation but the two of them showed significant correlations to Nt. Regression equations were calculated. Two group of plots were separated among the total 96 in the assay, and the minimum and maximum values of the related soil indexes were given. The group 1 was characterized by a minimum grain yield of ca. 14 Uha and group 11 by a maximum yield of 5 Uha. The minimum values fer group I and the maximum for group 11, as mg/kg in the 0-60 cm soillayer were, respectively : Nt 725 and 319 ; P-C02 1:103.68 and 2.43; Ke-NH4 180 and 147. In the 12 non fertilized plots the regression equation found between grain yield in kg/ha (Y) and total Nt mg/kg in the 0-60 cm soillayer was: Y =-3 393 + 24.04 X, r2 0.945 and the Standard error of estimation ± 916.